Chromogenic Photonic Crystals Enabled by Novel Vapor‐Responsive Shape‐Memory Polymers. (15th May 2015) - Fang, Yin; Ni, Yongliang; Choi, Baeck; Leo, Sin‐Yen; Gao, Jian; Ge, Beverly; Taylor, Curtis; Basile, Vito; Jiang, Peng
<x xml:space="preserve">Abstract</x> A new type of shape‐memory polymer (SMP) is developed by integrating scientific principles drawn from two disparate fields: the fast‐growing photonic crystal and SMP technologies. This new SMP enables room‐temperature operation for the entire shape‐memory cycle and instantaneous shape recovery triggered by exposure to a variety of organic vapors.